2021
DOI: 10.1186/s40359-021-00592-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the German version of the Opening Minds Stigma Scale for Health Care Providers (OMS-HC)

Abstract: Background Healthcare professionals can be a source of stigma and discrimination for people with mental illness, and anti-stigma programs are needed for this target group. However, there is no validated German language scale to assess attitudes of healthcare professionals towards people with mental illness. This study had the aim to validate the German language version of the Opening Minds Stigma Scale for Health Care Providers (OMS-HC), a self-report measure of stigmatizing attitudes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the validation results of the original validation, Cronbach’s alpha values of less than 0.70 were also obtained ( Modgill et al, 2014 ). In scale validation studies, it was also common for factors to have lower Cronbach’s alpha values, such as the studies conducted in Singapore ( Chang et al, 2017 ), Hungary ( Őri et al, 2020 ), Germany ( Zuaboni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the validation results of the original validation, Cronbach’s alpha values of less than 0.70 were also obtained ( Modgill et al, 2014 ). In scale validation studies, it was also common for factors to have lower Cronbach’s alpha values, such as the studies conducted in Singapore ( Chang et al, 2017 ), Hungary ( Őri et al, 2020 ), Germany ( Zuaboni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The OMS-HC validation studies conducted in European countries (Germany, Hungary and Italy) obtained slightly different results ( Destrebecq et al, 2018 ; Őri et al, 2020 ; Zuaboni et al, 2021 ). The German study showed good internal consistency for the total scale (α = 0.74) and lower for the three factors (α < 0.70), and the authors maintained the original factor structure ( Zuaboni et al, 2021 ). The Hungarian study ( Őri et al, 2020 ) also had good internal consistency (α = 0.73) and lower internal consistency for the three factors of the factor structure (α < 0.70).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…To assess the extent of stigmatisation of MHCPs toward their service users, attitudes toward individuals with mental illness were assessed using the Opening Minds Stigma Scale for Health Care Providers (OMS-HC) (Modgill et al, 2014;Zuaboni et al, 2021). The OMS-HC includes 15 items to be answered on a 5-point scale (1: strongly disagree to 5: strongly agree) with higher scores indicating more negative attitudes toward persons with mental illness (m = 1.81, SD = 0.41, Cronbach's α = 0.72).…”
Section: Variables and Instrumentsmentioning
confidence: 99%
“…For this reason, the authors revisited the factor structure of the scale in a larger and more representative sample consisting of various healthcare providers that resulted in a more stable, three-factor solution (attitude, disclosure and help-seeking, and social distance) with 15 items ( 5 ). Studies with different samples of healthcare providers have shown OMS-HC scores to be a reliable and valid measure of stigmatizing attitudes toward patients in Italy ( 6 ), Hungary ( 7 ), Germany and Switzerland ( 8 ), Chile ( 9 ), and Singapore ( 10 ). The three dimensions of attitude, disclosure and help-seeking, and social distance structure appear to be similar; however, in most of the international studies, some items were found to be weak and loaded on different factors than that of the Canadian version and theory.…”
Section: Introductionmentioning
confidence: 99%